2018
DOI: 10.1017/s1751731117002208
|View full text |Cite
|
Sign up to set email alerts
|

Feeding broilers with dry whey powder and whey protein concentrate affected productive performance, ileal digestibility of nutrients and cecal microbiota community

Abstract: Dietary interventions are a common practice in the poultry industry to promote optimal performance and health of animals. Here, we aim at assessing the influence of supplementing broiler diets with dry whey powder (DWP) and whey protein concentrate (WPC) on nutrient coefficient of apparent ileal digestibility (CAID) and productive performance. Cecal microbiota composition was also determined using Illumina amplicon sequencing. Dietary treatments were control diet (no supplementation of DWP or WPC), 60-DWP (60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…An improvement in bird's performance in the WP group may also be explained by highly digestible protein and fat and the presence of water‐soluble vitamins in WP (Kermanshahi & Rostami, ). Similarly, Pineda‐Quiroga et al () showed that the addition of WP to broiler diets increased average daily gain and body weight during the starter, grower, and the entire feeding periods compared to the CON. Ocejo et al () also reported that single or combined supplementation of WP and calcium butyrate improved growth performance, feed efficiency, and intestinal integrity of broiler chickens.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…An improvement in bird's performance in the WP group may also be explained by highly digestible protein and fat and the presence of water‐soluble vitamins in WP (Kermanshahi & Rostami, ). Similarly, Pineda‐Quiroga et al () showed that the addition of WP to broiler diets increased average daily gain and body weight during the starter, grower, and the entire feeding periods compared to the CON. Ocejo et al () also reported that single or combined supplementation of WP and calcium butyrate improved growth performance, feed efficiency, and intestinal integrity of broiler chickens.…”
Section: Discussionmentioning
confidence: 90%
“…In agreement with our findings, Alloui and Szczurek () found that the inclusion of whey lactose in broiler diets increased the concentration of LAB and volatile fatty acids, and reduced coliform bacteria and pH in the caecal contents. Pineda‐Quiroga et al () also reported a positive correlation between whey lactose and relative abundance of butyrate‐producing bacteria in ceca, which modulates gut microbiota. Whey lactose acts in a similar way as oligosaccharides do.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations